Acetabular cartilage delamination: performance of MRI using arthroscopy as the standard of reference. (March 2023) - Neumann, Jan; Zhang, Alan L; Bucknor, Matthew; Majumdar, Sharmila; Souza, Richard; Joseph, Gabby B; Link, Thomas M
Background: Femoroacetabular impingement (FAI) frequently leads to acetabular chondral delamination. Early identification and treatment of these cases is crucial to prevent further damage to the hip. Purpose: To evaluate the accuracy of morphological signs of cartilage acetabular delamination in non-arthrographic magnetic resonance imaging (MRI) using intra-articular arthroscopic findings in patients undergoing FAI surgery. Material and Methods: All hip MRI scans were assessed individually by three independent radiologists. Images were assessed for signs of delamination including the presence of a linear area of bright signal intensity along the acetabular subchondral bone and an area of darker tissue at the surface of the acetabular cartilage. All FAI patients underwent surgery; arthroscopy served as the standard of reference. Results: The mean age of participants was 36.1±10.9 years with 36 (48.6%) women. In the FAI group, arthroscopic surgery showed acetabular chondral delamination in 37 hips. In all hips (including the controls), MRI signs of acetabular cartilage delamination showed an average sensitivity across the three raters of 73.0% with a specificity of 71.0%. In a separate analysis of only the FAI patients, a slightly higher sensitivity (77.7%) but lower specificity (66.7%) was demonstrated. The interrater reliability showed a moderate agreement (average [k]) across the raters (0.450). Conclusion: Performance of non-arthrographic MRI in diagnosing acetabular chondral delamination showed good results, yet inter-observer reproducibility among different radiologists was only moderate. Our results suggest that an increased level of awareness, for signs of delamination using MRI, will be helpful for detecting chondral delamination in patients with a history of FAI.